Collage van BG A3/990, BG B1/641, De Vrije Socialist 1916, 26 februari en Recht voor Allen 1887, 7 september. Zie ook BG A4/8 en BG A4/27. Uit: archief F. Domela NIeuwenhuis, map VI a 1 A
Collage van BG A3/990, BG B1/641, De Vrije Socialist 1916, 26 februari en Recht voor Allen 1887, 7 september. Zie ook BG A4/8 en BG A4/27. Uit: archief F. Domela NIeuwenhuis, map VI a 1 A.